The Moon card of the Tarot deck may reprise an ancient amuletic design against the Evil Eye - Graham, Lloyd D. (Eikón / Imago, 2022)
This paper proposes a novel source for –or at least influence on– the iconography of the Moon trump in the Rider-Waite Tarot deck, which preserves the design from the Tarot de Marseille. In fact, the Moon template appears to date back to the earliest days of the Tarot. The proposed source or prototype is a Greco-Roman talismanic design against the Evil Eye known as the “all-suffering eye”, which frequently occupies the reverse face of Byzantine copper/ bronze “Holy Rider” amulets. The paper identifies compositional elements that correspond in the Evil Eye and Moon card designs, presents reasons why the moon and the Evil Eye might have been thought of as cognates, and considers other likely inputs into the Moon card’s visual program.